Comparative effectiveness of GLP-1 receptor agonists and dual agonists in the treatment of patients with metabolic dysfunction associated steatohepatitis: a systematic review and meta-analysis - Li, Meng; Hu, Jianli; Han Chin, Yip; Chew, Han Shi Jocelyn; Wang, Wenru (Frontiers in Endocrinology, 2025)
BackgroundGlucagon-like peptide-1 receptor agonists (GLP-1RAs) and dual agonists have been shown to induce histological improvements in patients with metabolic dysfunction-associated steatohepatitis (MASH). However, current clinical evidence on their effectiveness in improving hepatic fibrosis and cardiovascular outcomes remains limited and inconsistent.MethodsThis study synthesized randomized controlled trials (RCTs) from major databases up to August 30, 2025, focusing on patients with biopsy-confirmed MASH. Pooled mean differences were calculated using either a fixed-effects or random-effects model, depending on the degree of heterogeneity observed among the studies.ResultsSix studies including 1,726 participants were analyzed. Compared with placebo, GLP-1RAs and dual agonists significantly increased the likelihood of histological improvement in MASH without worsening hepatic fibrosis. (OR: 4.51, 95% CI: 3.68 to 5.52). It was associated with a ≥1-stage improvement in hepatic fibrosis without worsening MASH (OR: 1.78; 95% CI: 1.47to2.16). In addition, it contributed to MASH resolution accompanied by a ≥1-stage improvement in hepatic fibrosis (OR: 7.42; 95% CI: 2.98to18.48). In subgroup analyses based on post-treatment weight loss, GLP-1RAs and dual agonists demonstrated significant efficacy in promoting hepatic fibrosis resolution without worsening MASH among patients achieving a ≥10% weight loss (OR: 9.59; 95% CI: 4.01to15.18). However, in patients with <10% weight loss, GLP-1RAs and dual agonists did not demonstrate significant differences (OR: 1.30; 95% CI: 0.92to1.83). Moreover, GLP-1RAs and dual agonists achieved a significant pooled reduction in cardiovascular parameters, including total cholesterol (WMD: −4.15 mmol/L; 95% CI: −13.13 to 4.82) and triglycerides (WMD: −17.70 mmol/L; 95% CI: −21.95 to −13.44). Nevertheless, no significant improvement was observed in Low-Density Lipoprotein Cholesterol (LDL-C) levels (WMD: −0.67 mmol/L; 95% CI: −6.55 to 5.21).ConclusionIn patients with MASH who achieve a ≥10% weight loss, GLP-1RAs and dual agonists are associated with significant improvements in hepatic fibrosis, whereas their effect is limited in those with <10% weight loss. However, a significant reduction in LDL-C was observed only among patients achieving substantial (≥10%) weight loss. This finding suggests that for patients requiring comprehensive cardiovascular risk management, additional lipid-lowering strategies may be needed to optimize the effectiveness of the intervention.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025640318.